Poverty in a Sociological Perspective - Stoilova, Vyara (Research Papers, 2025)
The article focuses on poverty as one of the significant social problems of modern society. The aim of the analysis is to conceptualize some aspects of relative poverty in the context of the theoretical views of Georg Simmel (1858 – 1918). A special focus is the subjective feeling of poverty, which can also be found in people who are outside the “social territory” of relative poverty defined in society. The need for empirical research on the “normal situation of poverty” (Simmel) in conditions of deepening social inequalities is put forward.